Preparation method and application of Prussian blue nanocage / calcium chloride composite hygroscopic material
By synthesizing Prussian blue nanocages at room temperature and pouring CaCl2, Prussian blue nanocage/calcium chloride composite hygroscopic material is formed, which solves the problems of low adsorption efficiency and easy destruction of pore structure of existing hygroscopic materials, and achieves efficient adsorption and photothermal conversion.
Patent Information
- Application Number
- CN202310444323.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-24
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-04-24
AI Technical Summary
The existing hygroscopic materials have low adsorption efficiency, small adsorption amount, and easy to damage the pore structure, making it difficult to efficiently capture water vapor under low humidity conditions.
The new Prussian blue nanocage/calcium chloride composite hygroscopic material was used to synthesize the new Prussian blue nanocage by anisotropic chemical etching at room temperature, and CaCl2 was infused into it as a hygroscopic agent.
It realizes effective absorption of water vapor in the air at night, and photothermal conversion is carried out during the day to release water vapor, which improves moisture absorption efficiency and adsorption amount, and enhances the stability of the pore structure.
Smart Images

Figure CN116688957B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hygroscopic material preparation, in particular to a preparation method and application of a Prussian blue nano cage / calcium chloride composite hygroscopic material. Background Art
[0002] The United Nations Intergovernmental Panel on Climate Change reported that 3.2 billion people around the world are suffering from water shortages due to lack of water sources such as rivers, lakes and groundwater. There is an urgent need to find available water resources to solve this global problem.
[0003] Atmospheric water harvesting is a promising strategy to address water shortages. Existing atmospheric water harvesting materials have demonstrated the possibility of capturing water vapor directly from air at 100% relative humidity using fog capture and condensation dew collection methods. However, these methods have high humidity requirements (100% RH) and high energy consumption under low humidity conditions, which are demanding on installation location and time. Therefore, current atmospheric water harvesting technology is limited to high humidity and high temperature areas.
[0004] Porous adsorption atmospheric water harvesting has attracted widespread attention because of its higher water capture efficiency than fog under arid and low relative humidity climate conditions and lower energy consumption than condensation water collection. Adsorption-type atmospheric water harvesting systems include passive regeneration devices and active regeneration devices, which have a single cycle per day and multiple cycles per day, respectively. The passive regeneration atmospheric water harvesting process uses porous solids as adsorbents, regenerates by solar heating, and condenses at room temperature. It is an efficient and low-energy water capture technology. Therefore, constructing high-performance adsorbents with low desorption temperature, large adsorption capacity, and good hydrothermal stability is the key to the passive regeneration atmospheric water harvesting system. Previous studies have shown that atmospheric water harvesting equipment using porous crystalline materials as adsorbents can capture vapor in arid climates (10-40% RH) and has high water collection efficiency.
[0005] Metal-organic frameworks (MOFs) are typical porous multifunctional materials composed of metal centers / clusters bridged by functional organic ligands, which have attracted increasing attention in recent years. Their unique properties of high surface area and uniform porosity have potential applications in various fields such as gas storage / separation, drug delivery, sensors and catalysis. Summary of the invention
[0006] Purpose of the invention: Based on the hygroscopic properties and evaporation properties of hygroscopic materials, the present invention aims to solve the problems of low adsorption efficiency, small adsorption capacity and easily destroyed pore structure of existing hygroscopic materials, and discloses a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material.
[0007] Technical solution: A method for preparing a Prussian blue nanocage / calcium chloride composite hygroscopic material, comprising the following steps:
[0008] Step 1): preparing nickel-cobalt Prussian blue nanocubes;
[0009] Dissolving nickel nitrate and sodium citrate in distilled water to obtain solution A, and dissolving potassium hexacyanocobaltate in distilled water to obtain solution B; mixing solution A and solution B, stirring and aging the mixed solution for 1 to 7 days, washing and drying the reaction product to obtain nickel-cobalt Prussian blue nanocubes;
[0010] 2) Preparation of nickel-cobalt Prussian blue nanocages:
[0011] The nickel-cobalt Prussian blue nanocubes prepared in step 1) are dissolved in anhydrous ethanol to obtain a solution C, ammonia monohydrate is dissolved in deionized water to obtain a solution D, the solution C and the solution D are mixed, and stirred at room temperature for 0.5 to 9 hours, and the reaction product is washed, dried, and ground to obtain a nickel-cobalt Prussian blue nanocage;
[0012] 3) Preparation of Prussian blue nanocage / calcium chloride composite hygroscopic material:
[0013] The nickel-cobalt Prussian blue nanocages and calcium chloride prepared in step 2) are dissolved in deionized water and stirred for 8-12 hours. The reaction product is washed with deionized water and anhydrous ethanol and dried to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material.
[0014] Furthermore, in the step 3), the mass ratio of nickel-cobalt Prussian blue nanocage to calcium chloride is 200:(1072-4286).
[0015] Furthermore, in the step 1), the stirring time is 5 to 10 minutes.
[0016] Furthermore, the stirring method in step 1) to step 3) is magnetic stirring.
[0017] Furthermore, in the step 1), the molar ratio of nickel nitrate, sodium citrate and potassium hexacyanocobaltate is 1:(9-10):(4-5).
[0018] Furthermore, the washing method in step 1) to step 3) is centrifugal washing or suction filtration washing.
[0019] Furthermore, the grinding method in step 2) is manual grinding or ball mill grinding, and the grinding time is 0.5 to 2 hours.
[0020] The Prussian blue nanocage / calcium chloride composite hygroscopic material prepared by the above-mentioned preparation method can be used in the fields of hygroscopic warmth preservation, air water extraction, hygroscopic heat storage or hygroscopic refrigeration.
[0021] Beneficial effects:
[0022] 1. The composite hygroscopic material prepared by the present invention uses metal organic frameworks MOFs as the substrate, has the characteristics of high surface area and uniform porosity, and has potential applications in various fields such as gas storage / separation, drug delivery, sensors and catalysis.
[0023] 2. The novel Prussian blue nanocage synthesized by the present invention at room temperature by simple anisotropic chemical etching has a simple and easy-to-operate synthesis process and is conducive to large-scale production.
[0024] 3. The Prussian blue nanocage / calcium chloride composite hygroscopic material preferably prepared in the present invention can effectively absorb water vapor in the air at night and perform photothermal conversion to release water vapor during the day. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The SEM images of nickel-cobalt Prussian blue nanocages (PBA) prepared in Examples 1-5 of the present invention at different etching times;
[0026] Figure 2 Different amounts of CaCl were injected at different etching times prepared in Comparative Examples 1-6 of the present invention. 2 Prussian blue nanocage / calcium chloride composite hygroscopic material CaCl 2 / SEM image of PBA;
[0027] Figure 3 These are XRD images of PBA at different etching times in Examples 1-4 of the present invention.
[0028] Figure 4 The UV-Vis-NIR absorption spectra of PBA at different etching times in Examples 3-4 of the present invention.
[0029] Figure 5 Different amounts of CaCl were injected at the same etching time in Example 3 of the present invention and Comparative Example 1. 2 Prussian blue nanocage / calcium chloride composite hygroscopic material CaCl 2 FTIR spectrum of / PBA.
[0030] Figure 6 Different amounts of CaCl were injected into Comparative Examples 1-3 of the present invention. 2 Prussian blue nanocage / calcium chloride composite hygroscopic material CaCl 2 / PBA's moisture absorption capacity at 65% RH and after 1h of light exposure. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0032] Experimental reagents in the embodiment: nickel nitrate (NiN 2 O 6 ), sodium citrate (Na 3 C 6 H 5 O 7 ), potassium hexacyanocobaltate (C 6 CoK 3 N 6 ), ammonia monohydrate (NH 3 ·H 2 O), calcium chloride (CaCl 2 ) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0033] Example 1
[0034] This embodiment describes in detail a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material, including the following steps:
[0035] 1) Preparation of Nickel-Cobalt Prussian Blue Nanocubes (PB):
[0036] 0.174 g nickel nitrate and 0.256 g sodium citrate were dissolved in 20 mL distilled water, and 0.133 g potassium hexacyanocobaltate was dissolved in 20 mL distilled water. The two solutions were then mixed and aged for 1 day, centrifuged, washed, and dried to obtain nickel-cobalt Prussian blue nanocubes, denoted as PB.
[0037] 2) Preparation of Nickel-Cobalt Prussian Blue Nanocages (PBA):
[0038] 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, and 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water. The two solutions were then mixed, stirred at room temperature for 0.5 h, centrifuged, washed, dried, and ground to obtain nickel-cobalt Prussian blue nanocages, which were recorded as PBA-1.
[0039] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of PBA:
[0040] 0.200 g PBA-1 prepared in step 2) and 4.286 g calcium chloride were dissolved in 10 mL deionized water and stirred for 12 h, and then centrifuged, washed and dried with deionized water and anhydrous ethanol to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material, denoted as CaCl 2 / PBA-1.
[0041] Example 2
[0042] This embodiment describes in detail a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material, including the following steps:
[0043] 1) Preparation of Nickel-Cobalt Prussian Blue Nanocubes (PB):
[0044] 0.174 g of nickel nitrate and 0.256 g of sodium citrate were dissolved in 20 mL of distilled water, and 0.133 g of potassium hexacyanocobaltate was dissolved in 20 mL of distilled water. The two solutions were then mixed and aged for 1 day, centrifuged, washed, and dried to obtain nickel-cobalt Prussian blue nanocubes, denoted as PB;
[0045] 2) Preparation of nickel-cobalt Prussian blue nanocages (PBA): 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, and 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water. The two solutions were then mixed, stirred at room temperature for 1 h, centrifuged, washed, dried, and ground to obtain nickel-cobalt Prussian blue nanocages, which were recorded as PBA-2.
[0046] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of PBA:
[0047] 0.200 g PBA-2 prepared in step 2) and 4.286 g calcium chloride were dissolved in 10 mL deionized water and stirred for 12 h, and then centrifuged, washed and dried with deionized water and anhydrous ethanol to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material, denoted as CaCl 2 / PBA-2.
[0048] Example 3
[0049] This embodiment describes in detail a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material, including the following steps:
[0050] 1) Preparation of Nickel-Cobalt Prussian Blue Nanocubes (PB):
[0051] 0.174 g of nickel nitrate and 0.256 g of sodium citrate were dissolved in 20 mL of distilled water, and 0.133 g of potassium hexacyanocobaltate was dissolved in 20 mL of distilled water. The two solutions were then mixed and aged for 1 day, centrifuged, washed, and dried to obtain nickel-cobalt Prussian blue nanocubes, denoted as PB;
[0052] 2) Preparation of Nickel-Cobalt Prussian Blue Nanocages (PBA):
[0053] 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water, the two solutions were mixed, stirred at room temperature for 3 h, centrifuged, washed, dried and ground to obtain nickel-cobalt Prussian blue nanocages, which were recorded as PBA-3;
[0054] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of PBA:
[0055] 0.200 g PBA-3 prepared in step 2) and 4.286 g calcium chloride were dissolved in 10 mL deionized water and stirred for 12 h, and then centrifuged, washed and dried with deionized water and anhydrous ethanol to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material, denoted as CaCl 2 / PBA-3.
[0056] Example 4
[0057] This example describes in detail a method for preparing a Prussian blue nanocage / calcium chloride composite hygroscopic material, comprising the following steps:
[0058] 1) Preparation of Nickel-Cobalt Prussian Blue Nanocubes (PB):
[0059] 0.174 g of nickel nitrate and 0.256 g of sodium citrate were dissolved in 20 mL of distilled water, and 0.133 g of potassium hexacyanocobaltate was dissolved in 20 mL of distilled water. The two solutions were mixed and aged for 1 day, centrifuged, washed, and dried to obtain nickel-cobalt Prussian blue nanocubes, denoted as PB;
[0060] 2) Preparation of Nickel-Cobalt Prussian Blue Nanocages (PBA):
[0061] 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water, the two solutions were mixed, stirred at room temperature for 6 h, centrifuged, washed, dried, and ground to obtain nickel-cobalt Prussian blue nanocages, denoted as PBA-4;
[0062] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of Prussian blue nanocage / calcium chloride composite hygroscopic material: 0.200 g PBA-4 prepared in step 2) and 4.286 g calcium chloride were dissolved in 10 mL deionized water and stirred for 12 h. The composite hygroscopic material was washed by centrifugation with deionized water and anhydrous ethanol and dried to obtain Prussian blue nanocage / calcium chloride composite hygroscopic material, denoted as CaCl 2 / PBA-4.
[0063] Example 5
[0064] This embodiment describes in detail a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material, including the following steps:
[0065] 1) Preparation of Nickel-Cobalt Prussian Blue Nanocubes (PB):
[0066] 0.174 g of nickel nitrate and 0.256 g of sodium citrate were dissolved in 20 mL of distilled water, and 0.133 g of potassium hexacyanocobaltate was dissolved in 20 mL of distilled water. The two solutions were mixed and aged for 1 day, centrifuged, washed, and dried to obtain nickel-cobalt Prussian blue nanocubes, denoted as PB;
[0067] 2) Preparation of Nickel-Cobalt Prussian Blue Nanocages (PBA):
[0068] 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water, the two solutions were mixed, stirred at room temperature for 9 h, centrifuged, washed, dried, and ground to obtain nickel-cobalt Prussian blue nanocages, which were recorded as PBA-5;
[0069] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of PBA:
[0070] 0.200 g PBA-5 prepared in step 2) and 4.286 g calcium chloride were dissolved in 10 mL deionized water and stirred for 12 h, and then centrifuged, washed and dried with deionized water and anhydrous ethanol to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material, denoted as CaCl 2 / PBA-5.
[0071] Comparative Example 1
[0072] This embodiment describes in detail a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material, including the following steps:
[0073] 1) Preparation of Nickel-Cobalt Prussian Blue Nanocubes (PB):
[0074] 0.174 g of nickel nitrate and 0.256 g of sodium citrate were dissolved in 20 mL of distilled water, and 0.133 g of potassium hexacyanocobaltate was dissolved in 20 mL of distilled water. The two solutions were mixed and aged for 1 day, and then centrifuged, washed, and dried to obtain nickel-cobalt Prussian blue nanocubes, which were recorded as PB.
[0075] 2) Preparation of Nickel-Cobalt Prussian Blue Nanocages (PBA):
[0076] 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water, the two solutions were mixed, stirred at room temperature for 3 h, centrifuged, washed, dried and ground to obtain nickel-cobalt Prussian blue nanocages, denoted as PBA-3;
[0077] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of PBA:
[0078] 0.200 g PBA-3 and 2.143 g calcium chloride prepared in step 2) were dissolved in 10 mL deionized water and stirred for 12 h. The Prussian blue nanocage / calcium chloride composite hygroscopic material was obtained by centrifugation, washing and drying with deionized water and anhydrous ethanol and recorded as CaCl 2 / PBA-3-1 / 2.
[0079] Comparative Example 2
[0080] This example describes in detail a method for preparing a Prussian blue nanocage / calcium chloride composite hygroscopic material, comprising the following steps:
[0081] 1) Preparation of Nickel-Cobalt Prussian Blue Nanocubes (PB):
[0082] 0.174 g of nickel nitrate and 0.256 g of sodium citrate were dissolved in 20 mL of distilled water, and 0.133 g of potassium hexacyanocobaltate was dissolved in 20 mL of distilled water. The two solutions were mixed and aged for 1 day, centrifuged, washed, and dried to obtain nickel-cobalt Prussian blue nanocubes, denoted as PB;
[0083] 2) Preparation of Nickel-Cobalt Prussian Blue Nanocages (PBA):
[0084] 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water, the two solutions were mixed, stirred at room temperature for 3 h, centrifuged, washed, dried and ground to obtain nickel-cobalt Prussian blue nanocages, denoted as PBA-3;
[0085] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of PBA:
[0086] 0.200 g PBA-3 prepared in step 2) and 1.419 g calcium chloride were dissolved in 10 mL deionized water and stirred for 12 h, and then centrifuged, washed and dried with deionized water and anhydrous ethanol to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material, denoted as CaCl 2 / PBA-3-1 / 3.
[0087] Comparative Example 3
[0088] This embodiment describes in detail a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material, including the following steps:
[0089] 1) Preparation of Nickel-Cobalt Prussian Blue Nanocubes (PB):
[0090] 0.174 g of nickel nitrate and 0.256 g of sodium citrate were dissolved in 20 mL of distilled water, and 0.133 g of potassium hexacyanocobaltate was dissolved in 20 mL of distilled water. The two solutions were mixed and aged for 1 day, centrifuged, washed, and dried to obtain nickel-cobalt Prussian blue nanocubes, denoted as PB;
[0091] 2) Preparation of Nickel-Cobalt Prussian Blue Nanocages (PBA):
[0092] 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water, the two solutions were mixed, stirred at room temperature for 3 h, centrifuged, washed, dried and ground to obtain nickel-cobalt Prussian blue nanocages, denoted as PBA-3;
[0093] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of PBA:
[0094] 0.200 g PBA-3 and 1.072 g calcium chloride prepared in step 2) were dissolved in 10 mL deionized water and stirred for 12 h, washed by centrifugation with deionized water and anhydrous ethanol, and dried to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material, denoted as CaCl 2 / PBA-3-1 / 4.
[0095] Comparative Example 4
[0096] This embodiment describes in detail a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material, including the following steps:
[0097] 1) Preparation of nickel-cobalt Prussian blue nanocubes (PB): 0.174 g nickel nitrate and 0.256 g sodium citrate were dissolved in 20 mL distilled water, 0.133 g potassium hexacyanocobaltate was dissolved in 20 mL distilled water, and the two solutions were mixed, stirred, and then the solution was divided into two parts, centrifuged, washed, and dried to obtain nickel-cobalt Prussian blue nanocubes, denoted as PB;
[0098] 2) Preparation of nickel-cobalt Prussian blue nanocages (PBA): 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water, the two solutions were mixed, stirred at room temperature for 6 h, centrifuged, washed, dried and ground to obtain nickel-cobalt Prussian blue nanocages, denoted as PBA-4;
[0099] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of PBA:
[0100] 0.200 g PBA-4 prepared in step 2) and 2.143 g calcium chloride were dissolved in 10 mL deionized water and stirred for 12 h, washed by centrifugation with deionized water and anhydrous ethanol, and dried to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material, denoted as CaCl 2 / PBA-4-1 / 2.
[0101] Comparative Example 5
[0102] This embodiment describes in detail a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material, including the following steps:
[0103] 1) Preparation of Nickel-Cobalt Prussian Blue Nanocubes (PB):
[0104] 0.174 g of nickel nitrate and 0.256 g of sodium citrate were dissolved in 20 mL of distilled water, and 0.133 g of potassium hexacyanocobaltate was dissolved in 20 mL of distilled water. The two solutions were mixed and aged for 1 day, centrifuged, washed, and dried to obtain nickel-cobalt Prussian blue nanocubes, denoted as PB;
[0105] 2) Preparation of Nickel-Cobalt Prussian Blue Nanocages (PBA):
[0106] 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water, the two solutions were mixed, stirred at room temperature for 6 h, centrifuged, washed, dried, and ground to obtain nickel-cobalt Prussian blue nanocages, denoted as PBA-4;
[0107] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of PBA:
[0108] 0.200 g PBA-4 and 1.429 g calcium chloride prepared in step 2) were dissolved in 10 mL deionized water and stirred for 12 h, washed by centrifugation with deionized water and anhydrous ethanol, and dried to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material, denoted as CaCl 2 / PBA-4-1 / 3.
[0109] Comparative Example 6
[0110] This embodiment describes in detail a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material, including the following steps:
[0111] 1) Preparation of Nickel-Cobalt Prussian Blue Nanocubes (PB):
[0112] 0.174 g of nickel nitrate and 0.256 g of sodium citrate were dissolved in 20 mL of distilled water, and 0.133 g of potassium hexacyanocobaltate was dissolved in 20 mL of distilled water. The two solutions were mixed and aged for 1 day, centrifuged, washed and dried to obtain nickel-cobalt Prussian blue nanocubes, which were recorded as PB.
[0113] 2) Preparation of Nickel-Cobalt Prussian Blue Nanocages (PBA):
[0114] 0.02 g of PB prepared in step 1) was dissolved in 10 mL of ethanol, 2.5 mL of monohydrated ammonia was dissolved in 20 mL of water, the two solutions were mixed, stirred at room temperature for 6 h, centrifuged, washed, dried, and ground to obtain nickel-cobalt Prussian blue nanocages, denoted as PBA-4;
[0115] 3) Prussian blue nanocage / calcium chloride composite hygroscopic material (CaCl 2 Preparation of Prussian blue nanocage / calcium chloride composite hygroscopic material: 0.200 g PBA-4 prepared in step 2) and 1.072 g calcium chloride were dissolved in 10 mL deionized water and stirred for 12 h, washed by centrifugation with deionized water and anhydrous ethanol, and dried to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material, denoted as CaCl 2 / PBA-4-1 / 4.
[0116] The test results of Prussian blue nanocage / calcium chloride composite hygroscopic material are as follows:
[0117] Figure 1 The SEM images of the nickel-cobalt Prussian blue nanocages prepared in Examples 1-5 of the present invention at different etching times. Etching refers to the operation of step 2) of the present invention; wherein (a) PB is prepared in Example 1; (bc) PBA-1; (de) PBA-2; (fg) PBA-3; (hi) PBA-4; (jk) PBA-5; It can be seen from the figure that as the etching time increases, the nanocage gradually collapses, wherein the cube shape of the etching 3h (fg) and the etching 6h (hi) is relatively the best, which is conducive to multiple refraction of light in it and improves the photothermal conversion efficiency.
[0118] Figure 2 Different amounts of CaCl were injected at different etching times prepared in Comparative Examples 1-6 of the present invention. 2SEM images of Prussian blue nanocage / calcium chloride composite hygroscopic material CaCl2 / PBA: (a) CaCl 2 / PBA-3-1 / 2; (b)CaCl 2 / PBA-3-1 / 3; (c)CaCl 2 / PBA-3-1 / 4; (d)CaCl 2 / PBA-6-1 / 2; (e)CaCl 2 / PBA-6-1 / 3; (f)CaCl 2 / PBA-6-1 / 4; From the figure, it can be seen that compared with the nanocages etched for 6 hours, the nanocages etched for 3 hours are more three-dimensional and full. Under the same etching time, 1 / 2CaCl 2 The edges of the nanocages are clearer, and without affecting the morphology, CaCl 2 The higher the content, the more water vapor can be obtained from the air.
[0119] Figure 3 The XRD images of PBA at different etching times in Examples 1 to 4 of the present invention are shown in Figure 1. Compared with the XRD characteristic peaks of the original PB, the characteristic peaks of PBA after different etching times remain basically unchanged, indicating that the crystal structure of PB does not change after etching, among which PBA-3 and PBA-4 have the best crystallinity.
[0120] Figure 4 The UV-Vis-NIR absorption spectra of PBA at different etching times in Examples 3-4 of the present invention are shown in Table 1. The light absorption capacity of PBA-3 and PBA-4 was studied. Compared with PBA-4, PBA-3 showed better light absorption capacity at 1500-2000nm wavelength.
[0121] Figure 5 The Prussian blue nano cage / calcium chloride composite hygroscopic material CaCl2 was injected with different amounts of CaCl2 at the same etching time in Example 3 of the present invention and Comparative Example 1. 2 FTIR spectrum of / PBA. The peaks at 1419, 1604 and 3370 cm -1 The characteristic peaks of are attributed to -OH, C=C, OH, respectively. The appearance of hydrophilic groups is conducive to the hygroscopic material to better absorb moisture from the air. 2 / PBA-3 and CaCl 2 / PBA-3-1 / 2, CaCl 2 The characteristic peak of / PBA-3-1 / 2 is narrower and sharper, indicating that the perfusion of CaCl 2 The presence of hydrophilic groups is more obvious.
[0122] Figure 6Different amounts of CaCl were injected into Comparative Examples 1-3 of the present invention. 2 Prussian blue nanocage / calcium chloride composite hygroscopic material CaCl 2 / PBA's moisture absorption capacity at 65% RH and after 1h of light exposure.
[0123] At 65%RH, CaCl 2 / PBA-3-1 / 2 has the best moisture absorption capacity, reaching 0.16g / g, and at 1kWm 2 Under light intensity, its mass loss is 0.17g.
[0124] It can be seen from the above examples 1-5 and comparative examples 1-6 that the present invention solves the problems and shortcomings of the conventional technology, starting from the evaporation performance and economic performance of the photothermal material, and targeting the problems of low adsorption efficiency, small adsorption amount and easily damaged pore structure of the existing hygroscopic materials, a preparation method and application of a Prussian blue nanocage / calcium chloride composite hygroscopic material is provided. The present invention synthesizes a novel Prussian blue simulated cubic nanocage composed of pyramid-shaped walls by a simple anisotropic chemical etching route at room temperature, and then perfuses CaCl 2 As a desiccant, the final Prussian blue nanocage / calcium chloride composite hygroscopic material is formed, which can be used in the fields of moisture absorption and warmth preservation, air water extraction, moisture absorption and heat storage, moisture absorption and refrigeration. It can effectively absorb water vapor in the air at night, and perform photothermal conversion to release water vapor during the day.
[0125] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.
Claims
1. A method for preparing a Prussian blue nanocage / calcium chloride composite hygroscopic material, characterized in that: The following steps are involved: Step 1): preparing nickel-cobalt Prussian blue nanocubes; Dissolving nickel nitrate and sodium citrate in distilled water to obtain solution A, and dissolving potassium hexacyanocobaltate (III) in distilled water to obtain solution B; mixing solution A and solution B, stirring and aging the mixed solution for 1 to 7 days, washing and drying the reaction product to obtain nickel-cobalt Prussian blue nanocubes; 2) Preparation of nickel-cobalt Prussian blue nanocages: The nickel-cobalt Prussian blue nanocubes prepared in step 1) are dissolved in anhydrous ethanol to obtain a solution C, ammonia monohydrate is dissolved in deionized water to obtain a solution D, the solution C and the solution D are mixed, and stirred at room temperature for 0.5 to 9 hours, and the reaction product is washed, dried, and ground to obtain a nickel-cobalt Prussian blue nanocage; 3) Preparation of Prussian blue nanocage / calcium chloride composite hygroscopic material: The nickel-cobalt Prussian blue nanocages and calcium chloride prepared in step 2) are dissolved in deionized water and stirred for 8-12 hours. The reaction product is washed with deionized water and anhydrous ethanol and dried to obtain a Prussian blue nanocage / calcium chloride composite hygroscopic material.
2. The method for preparing a Prussian blue nanocage / calcium chloride composite hygroscopic material according to claim 1, characterized in that: In the step 3), the mass ratio of nickel-cobalt Prussian blue nanocage to calcium chloride is 200:(1072-4286).
3. The method for preparing a Prussian blue nanocage / calcium chloride composite hygroscopic material according to claim 1, characterized in that: In the step 1), the stirring time is 5 to 10 minutes.
4. The method for preparing a Prussian blue nanocage / calcium chloride composite hygroscopic material according to claim 1, characterized in that: The stirring method in steps 1) to 3) is magnetic stirring.
5. The method for preparing the Prussian blue nano cage / calcium chloride composite hygroscopic material according to claim 1, characterized in that: In the step 1), the molar ratio of nickel nitrate, sodium citrate and potassium hexacyanocobaltate (III) is 1: (9-10): (4-5).
6. The method for preparing the Prussian blue nano cage / calcium chloride composite hygroscopic material according to claim 1, characterized in that: The washing method in step 1) to step 3) is centrifugal washing or suction filtration washing.
7. The method for preparing the Prussian blue nano cage / calcium chloride composite hygroscopic material according to claim 1, characterized in that: The grinding method in step 2) is manual grinding or ball mill grinding, and the grinding time is 0.5 to 2 hours.
8. The Prussian blue nanocage / calcium chloride composite hygroscopic material prepared by the preparation method according to any one of claims 1 to 7.
9. Application of the Prussian blue nanocage / calcium chloride composite hygroscopic material prepared by the preparation method according to any one of claims 1 to 7 in hygroscopic warmth retention, air water extraction, hygroscopic heat storage or hygroscopic refrigeration.
Citation Information
Patent Citations
Method for in-situ preparation of 3D hollow macroporous Co / Fe PBA nanocage structure material through one-pot method and application of 3D hollow macroporous Co / Fe PBA nanocage structure material
CN114873611A
Particulate exothermic warm cosmetic with good storage stability
JP2007262006A